The refuge of affections : family and American reform politics, 1900-1920 - Rauchway, Eric (Columbia University Press, 2001)
The Progressives-those reformers responsible for the shape of many American institutions, from the Federal Reserve Board to the New School for Social Research-have always presented a mystery. What prompted middle-class citizens to support fundamental change in American life? Eric Rauchway shows that like most of us, the reformers took their inspiration from their own lives-from the challenges of forming a family. Following the lives and careers of Charles and Mary Beard, Wesley Clair and Lucy Sprague Mitchell, and Willard and Dorothy Straight, the book moves from the plains of.
Keywords: Social reformers -- United States -- Biography.; Families -- United States.; Progressivism (United States politics); Réformateurs sociaux -- États-Unis -- Biographies.; Familles -- États-Unis.; Progressisme -- États-Unis.; SOCIAL SCIENCE -- General.; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists.; HISTORY -- United States -- 20th Century.; Families; Social reformers; United States; Familie; Sozialreformer; Progressismus; USA; Sociale verandering.; collective biographies.; Biographies; Biographies.